Group counselling with self-control technique to reduce gadget addiction - Nur Azizah; M. Harwansyah Putra Sinaga (Program Studi bimbingan Konseling PPs UNM Makassar, 2024)
This study aims to explore the gadget addiction among MAN 2 Deli Serdang students and the success rate of group counseling with self-control techniques in overcoming the addiction. This study used a quantitative approach with experimental research design and employed data collection tools of interviews, observations, and psychological scales of gadget addiction. A total of 59 students were involved, in which the research sample amounted to 18 people divided into two groups with each consisting of 9 students in the experimental group and control group. The sample selection was done through purposive sampling technique. Analysis of differences in gadget addiction scores before and after counseling sessions was calculated using the Wilcoxon test. The findings showed that the mean score of gadget addiction in MAN 2 Deli Serdang was 68, which placed it in the moderate category. This signifies that gadget addiction in this institution is at moderate level. Group counseling with self-control techniques is proven effective, which is evident from the results of statistical analysis using the Wilcoxon test with a p-value of 0.008. With this p-value lower than 0.05, both in pretest and posttest, it shows that self-control technique has a positive impact in reducing gadget addiction in MAN 2 Deli Serdang.